Respuesta :

Answer:

the answer is 12

Step-by-step explanation:

Answer:

Second option

[tex]x =9[/tex]

Step-by-step explanation:

To solve this problem we use the secant theorem.

If two secant lines intersect with a circumference, the product between the segment external to the circumference and the total segment in one of the secant lines is equal to the product of the corresponding segments in the other secant line.

This means that

[tex](5+4)*4 = (x+3)*3[/tex]

Now we solve the equation for the variable x

[tex](9)*4 = (x+3)*3[/tex]

[tex]36 = 3x + 9[/tex]

[tex]36-9 = 3x[/tex]

[tex]3x =27[/tex]

[tex]x =9[/tex]